2004
DOI: 10.1161/01.atv.0000143857.27408.de
|View full text |Cite
|
Sign up to set email alerts
|

β3-Integrin Regulates Vascular Endothelial Growth Factor-A–Dependent Permeability

Abstract: Objective— β3-integrin deficiency has been implicated in increasing levels of Flk-1 expression on endothelial cells and enhancing vascular endothelial growth factor (VEGF)-induced angiogenesis. We determined the role of β3-integrin in mediating VEGF-A–induced blood vessel permeability through Flk-1. Methods and Results— Using the Miles assay, we demonstrated that VEGF-A–induced plasma leakage was enhanced in β3-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 55 publications
3
113
1
2
Order By: Relevance
“…When analyzing the vasculature, morphologic changes in endothelial cells are observed in tumors, liver, and heart. These display certain common features, such as irregular and hypertrophic cytoplasm with extensions projecting toward the capillary lumen that show no immediate similarities to those observed in other mouse models exhibiting pathologic vascular phenotypes (9,(35)(36)(37)(38)(39)(40)(41). In Pdgf-b-deficient or Pdgfr-b-deficient mice, fetal brain endothelial cells display an altered endothelial cell morphology that partly resembles the changes presently observed (42).…”
Section: Discussionmentioning
confidence: 82%
“…When analyzing the vasculature, morphologic changes in endothelial cells are observed in tumors, liver, and heart. These display certain common features, such as irregular and hypertrophic cytoplasm with extensions projecting toward the capillary lumen that show no immediate similarities to those observed in other mouse models exhibiting pathologic vascular phenotypes (9,(35)(36)(37)(38)(39)(40)(41). In Pdgf-b-deficient or Pdgfr-b-deficient mice, fetal brain endothelial cells display an altered endothelial cell morphology that partly resembles the changes presently observed (42).…”
Section: Discussionmentioning
confidence: 82%
“…In contrast to previous studies on the effect of the global genetic ablation of ␣v␤3 or ␣2␤1 on angiogenesis, 29,30,[45][46][47] which includes the effects of the deletion of these integrins in many cell types on neovascularization, our study is the first to dissect the precise role of ␣3␤1 integrin in endothelial cells in vivo. It is noteworthy that although ␣v␤3-integrin deficiency also enhances angiogenic responses by elevating Flk-1 levels, 29,30,45 and that endothelial ␣6 integrin deficiency is associated with increased Flk-1 levels, 48 the regulation of Flk-1 is at the transcriptional level in the ␣3-null endothelial cells but at the protein level in ␤3-null and ␣6-null endothelial cells. This difference suggests that, although the regulation of angiogenesis by these integrins converge on Flk-1, the mechanisms by which they do so are different.…”
Section: Discussionmentioning
confidence: 85%
“…Previous findings have suggested that ␤3-null mice have no vascular defect. 5,[7][8][9] After examining the coronary vasculature of ␤3-null mice during the phase of VEGF-dependent postnatal vascular remodeling in the heart, we found that myocyte growth and angiogenesis was similar between genotypes. Specifically, there is no evidence that the vascular organization or coronary capillary density is different in the ␤3-null mouse heart after careful evaluation using immunohistochemistry and intravenous lectin perfusion (data not shown).…”
Section: Resultsmentioning
confidence: 95%
“…The ␤3-null mouse shows defects in platelet aggregation and bleeding 7 as well as enhanced vascular endothelial growth factor (VEGF)-induced endothelial-cell migration, proliferation, permeability, and angiogenesis. 5,8 Enhanced tumor growth in ␤3-null mice has been attributed to increased endothelial-cell expression of the VEGF receptor Flk-1/KDR 9 and decreased macrophage infiltration. 9,10 ␤3-null mice also have enhanced inflammatory 11 and wound healing responses, 12 the latter due to increased fibroblast infiltration and increased TGF-␤1 expression.…”
Section: Introductionmentioning
confidence: 99%